Dynamic modeling of hydro- formylation of 1-decene on Rh/C catalyst in bubble colunm slurry reactor - Upkare, Makarand M.; Rajurkar, Kalpendra B.; Das, Samir K.; Jaganathan, Rengaswamy (International Conference on Modeling, Optimization, and Computing, 2010)
A dynamic model has been developed for the bubble column slurry reactor operating under non-isothermal conditions. The model consists of mass and heat balance equations for the gas and liquid phases and the catalyst particle. The model equations consisted of partial differential equations (PDE) which were converted to ordinary differential equations (ODE) by using finite difference relationships for the spatial derivatives and the ordinary differential equations for the time derivatives (Numerical Method of Lines-NMoL). The model was applied to describe the dynamic behaviour of bubble column slurry reactor during the hydroformylation of 1-decene on Rh/C catalyst. Model simulations were performed to obtain a meaningful path to steady state and to reproduce the other characteristics of the dynamic behaviour of the reactor. Under given conditions, the reaction required approximately 3750 seconds to reach the steady state concentrations at various reactor positions. It was observed with increase in the fluid velocities, the dynamics of the system was altered to 2500 seconds to reach the steady state condition. The effect of axial dispersion on the substrate concentration and the temperature rise along the reactor was further studied and discussed.
Keywords: axial dispersion; bubble column slurry reactor; Dynamic modeling; method of line; PDE solutions